2006
DOI: 10.1115/1.2401189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wall Calcifications in Patient-Specific Wall Stress Analyses of Abdominal Aortic Aneurysms

Abstract: It is generally acknowledged that rupture of an abdominal aortic aneurysm (AAA) occurs when the stress acting on the wall over the cardiac cycle exceeds the strength of the wall. Peak wall stress computations appear to give a more accurate rupture risk assessment than AAA diameter, which is currently used for a diagnosis. Despite the numerous studies utilizing patient-specific wall stress modeling of AAAs, none investigated the effect of wall calcifications on wall stress. The objective of this study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 19 publications
1
105
1
Order By: Relevance
“…Although, there is a lack of agreement on how calcifications actually affect it. Since the discussed constituent is stiffer than the rest of the wall, it presents possible stress concentration which is consistent with higher rupture probability [32,33]. On the other hand, calcifications cause local wall thickening [11] and demonstrate significant loadbearing effects, which results in lowering the wall stress [34].…”
Section: Presence Of Intraluminal Thrombus and Calcifications In Aaa mentioning
confidence: 71%
See 1 more Smart Citation
“…Although, there is a lack of agreement on how calcifications actually affect it. Since the discussed constituent is stiffer than the rest of the wall, it presents possible stress concentration which is consistent with higher rupture probability [32,33]. On the other hand, calcifications cause local wall thickening [11] and demonstrate significant loadbearing effects, which results in lowering the wall stress [34].…”
Section: Presence Of Intraluminal Thrombus and Calcifications In Aaa mentioning
confidence: 71%
“…It is important to employ ECG-gaited CT in order to obtain AAA geometry in diastolic phase of cardiac cycle. Some studies presented results of FEM analysis after applying the full systolic pressure to AAA model [32,52]. The used systolic pressure is either obtained from the patient or assumed as a value from the range 110-130 mm Hg.…”
Section: Loadingsmentioning
confidence: 99%
“…For stiffer calcifications, however, the different modeling approaches and the different geometries lead to significantly different results. A recent study confirmed that calcifications can significantly influence the local wall stress [43]. This indicates the importance of further study into methods for accurately determining and modeling the vessel wall material properties.…”
Section: Wall-stress Modelingmentioning
confidence: 92%
“…The material properties reported in literature for calcifications and the material properties actually used for simulations show great variation. Previous studies have focused on simplified modeling of the calcification shapes within a realistic aneurysm shape [20,42]. In our study, an accurate representation of the calcification geometry and a simplified model for the AAA were used.…”
Section: Wall Stress Simulationsmentioning
confidence: 99%
“…The aortic wall was assumed to have a uniform thickness of 1.9mm [10,20,25], and was modeled as a non-linear hyperelastic material [10]. These boundary conditions have been implemented in many previous studies [10,19,21,22,24,[26][27][28]. …”
Section: Finite Element Analysis (Fea)mentioning
confidence: 99%